Excitations in layered materials from a non-empirical Wannier-localized optimally-tuned screened range-separated hybrid functional - María Camarasa-Gómez; Stephen E. Gant; Guy Ohad; Jeffrey B. Neaton; Ashwin Ramasubramaniam; Leeor Kronik (npj Computational Materials)
Abstract Accurate prediction of electronic and optical excitations in van der Waals (vdW) materials is a long-standing challenge for density functional theory. The recent Wannier-localized optimally-tuned screened range-separated hybrid (WOT-SRSH) functional has proven successful in non-empirical determination of electronic band gaps and optical absorption spectra for covalent and ionic crystals. However, for vdW materials the tuning of the material- and structure-dependent functional parameters has only been attained semi-empirically. Here, we present a non-empirical WOT-SRSH approach applicable to vdW materials, with the optimal functional parameters transferable between monolayer and bulk. We apply this methodology to prototypical vdW materials: black phosphorus, molybdenum disulfide, and hexagonal boron nitride (in the latter case including zero-point renormalization). We show that the WOT-SRSH approach consistently achieves accuracy levels comparable to experiments and many-body perturbation theory (MBPT) calculations for band structures and optical absorption spectra, both on its own and as an optimal starting point for MBPT calculations.